Micro-nano needle phosphate antibacterial multifunctional coating as well as preparation method and application thereof
The preparation of micro-nano needle phosphate coatings through hydrothermal method solves the problem of insufficient antibacterial and bone performance in the prior art, and achieves an efficient and safe coating effect. It is suitable for medical implants and marine equipment parts, improving biocompatibility and corrosion resistance.
Patent Information
- Application Number
- CN202410150684.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2025-08-05
AI Technical Summary
It is difficult to prepare a micro-nanostructured phosphate coating that has both antibacterial and bone-promoting properties, and conventional methods have problems with complex coating interfaces and the introduction of multiple substances, resulting in limited coating effects or toxic side effects.
The micro-nano needle phosphate coating is prepared by hydrothermal method, and the longitudinal optimal growth of grains is regulated by chelating agent to form a micro-nano needle structural coating. Combined with zinc, strontium and other elements, the preparation process is simple and non-toxic and harmless. The coating is contact-resistant and suitable for medical implants and marine equipment parts.
The prepared micro-nano needle phosphate coating has high antibacterial activity and bone-promoting effect. It is suitable for long-term medical implantable devices, reduces the biotoxicity brought by zinc ion release, improves biocompatibility, and has good corrosion protection performance.
Smart Images

Figure HDA0004695566340000011 
Figure HDA0004695566340000012 
Figure HDA0004695566340000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of phosphate coatings, and particularly relates to a micro-nano needle phosphate antibacterial multifunctional coating, a preparation method thereof, and an application thereof. Background Art
[0002] In recent years, due to different accidents such as trauma, the number of fracture patients has increased rapidly. In addition, due to long-term tooth loss, periodontal diseases and other reasons in clinical practice, the demand for implants such as orthopedic implants and dental implants has been increasing continuously. Moreover, for surgical implant operations that require a certain amount of bone augmentation and bone repair, metal materials such as stainless steel, cobalt-chromium alloy, and titanium alloy are used for the repair of reconstructing bone tissue morphology and function. However, these implant materials often do not have or have a weak osteogenic effect. Therefore, surface modification technology can not only improve the biocompatibility of implants but also endow them with certain osteoinductivity. Among them, hydroxyapatite is the most important inorganic component of human bone, alveolar bone, and teeth. Strontium and calcium belong to the same group of alkali metals and have similar biological activities. Calcium and strontium-based phosphate substances are widely used in the surface coatings of medical implants. The hydrothermal synthesis method is a method for preparing phosphate coatings, which has the advantages of low cost and easy operation, and is widely used in the production industry.
[0003] For implant surgeries, the proportion of postoperative bacterial infections is extremely high, which is one of the main reasons for implant failure and seriously threatens the health of patients. At present, antibiotics are the conventional means to reduce the infection rate after implantation. However, due to its poor long-term treatment effect, serious complications, and increased bacterial strain resistance, it has gradually been replaced by other bactericides. The antibacterial effects of silver, copper, zinc and other ions are limited in time, and they have large cytotoxic side effects. These are all intractable problems in the prevention and treatment of implant infections. Therefore, it is crucial to endow metal materials with long-lasting, highly efficient and safe antibacterial properties.
[0004] Preparing antibacterial coatings by surface modification technology can eliminate the initial bacterial attachment and prevent the subsequent formation of biofilms, which is considered an effective method to avoid such events. In order to improve the antibacterial performance of the coating, people usually introduce some antibacterial components to achieve antibacterial by release. However, the antibacterial effect of such methods is limited, and some even have toxic side effects. Although the calcium, strontium and other based phosphate coatings prepared by conventional methods have good biocompatibility and certain osteogenic properties, they lack antibacterial functions.
[0005] Therefore, the development of micro-nano structured calcium, strontium and other based phosphate coatings with both antibacterial and osteogenic properties is of great significance for the clinical application of metal implant materials. Such antibacterial coatings can also be used to enhance the antibacterial function of the surfaces of titanium alloy, magnesium alloy, aluminum alloy, steel, etc. that are widely used in various marine equipment parts, so as to reduce the attachment of various microorganisms on the material surface and avoid material corrosion caused by microorganisms.
[0006] One of the problems to be solved is how to prepare a phosphate coating with a micro-nano needle structure that has good antibacterial effects and apply it in the fields of antibacterial, bone formation promotion, and corrosion mitigation. SUMMARY OF THE INVENTION
[0007] In order to overcome the deficiencies in the production methods of existing long-lasting, highly efficient, and safe antibacterial coatings, as well as the problems such as the need for multi-stage composite coatings to achieve antibacterial, osteogenic, and corrosion protection, complex preparation processes for composite coatings, and the introduction of various substances and coating interfaces, the primary object of the present invention is to provide a method for preparing a micro-nano needle phosphate antibacterial multi-functional coating.
[0008] Another object of the present invention is to provide the micro-nano needle phosphate antibacterial multi-functional coating prepared by the above method.
[0009] Another object of the present invention is to provide the application of the micro-nano needle phosphate antibacterial multi-functional coating in the fields of antibacterial, bone formation promotion, and corrosion mitigation. The antibacterial coating is used in medical implant materials (including bone repair materials, etc.) or anti-corrosion materials for slowing down the corrosion of marine equipment components.
[0010] The objects of the present invention are achieved through the following technical solutions:
[0011] A method for preparing a micro-nano needle phosphate antibacterial multi-functional coating, comprising the following steps:
[0012] 1) Prepare solutions of metal salts, phosphates, and chelating agents respectively using water;
[0013] 2) Mix the chelating agent solution with the metal salt solution to obtain a mixed solution; mix the phosphate solution with the mixed solution and adjust the pH to 8 - 12 to obtain a reaction solution;
[0014] 3) Immerse a clean substrate material into the reaction solution and perform a hydrothermal reaction to obtain a micro-nano needle phosphate coating on the surface of the substrate material;
[0015] The conditions for the hydrothermal reaction are a temperature of 60 - 160 °C and a time of 0.2 - 48 h.
[0016] The clean substrate material in step 3) refers to the substrate material obtained by cleaning.
[0017] The substrate material is at least one of zinc, zinc alloy, magnesium, magnesium alloy, iron, iron alloy, titanium, titanium alloy, tantalum, tantalum alloy, aluminum, aluminum alloy, or the corresponding porous materials of the above materials or the materials after the surface treatment of the above metals.
[0018] The cleaning is to clean the substrate material with at least one of dishwashing liquid, scouring powder, and organic solvents. The organic solvents are ethanol, acetone, etc. The cleaning is preferably ultrasonic cleaning with absolute ethanol.
[0019] The metal salts described in step 1) include at least one of calcium nitrate, calcium chloride, strontium nitrate, and strontium chloride; and at least one of any soluble salts containing bioactive elements such as magnesium, zinc, manganese, copper, silver, silicon, fluorine, cobalt, and selenium is not added or added.
[0020] The phosphate in step 1) is at least one of potassium dihydrogen phosphate, potassium hydrogen phosphate, potassium phosphate, sodium dihydrogen phosphate, sodium hydrogen phosphate, sodium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.
[0021] The chelating agents described in step 1) are at least one of ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, trisodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, dipotassium ethylenediaminetetraacetate, tripotassium ethylenediaminetetraacetate, tetrapotassium ethylenediaminetetraacetate, diammonium ethylenediaminetetraacetate, triammonium ethylenediaminetetraacetate, tetraammonium ethylenediaminetetraacetate, sodium iron ethylenediaminetetraacetate, iminodisuccinic acid, sodium iminodisuccinate, potassium iminodisuccinate and other iminodisuccinic acids and salts, diethylenetriaminepentaacetic acid, sodium diethylenetriaminepentaacetate, ethylene glycol bis(2-aminoethyl ether) tetraacetic acid, ethylene glycol bis(2-aminoethyl ether) tetraacetate tetrasodium, ethylene glycol bis(2-aminoethyl ether) tetraacetate tetrapotassium, etc.
[0022] The molar ratio of the metal salt, phosphate, and chelating agent in step 2) is 5 to 1000: 3 to 600: 5 to 1000; preferably (0.5 to 5): 1: (0.5 to 5), and more preferably (1 to 2.5): 1: (1 to 2.5).
[0023] The concentration of the metal salt solution in step 1) is 5 to 1000 mmol / L; preferably 10 to 800 mmol / L.
[0024] The concentration of the phosphate solution in step 1) is 3 to 600 mmol / L; preferably 6 to 500 mmol / L.
[0025] [[ID=2I]]The concentration of the chelating agent solution in step 1) is 5 to 1000 mmol / L; preferably 10 to 800 mmol / L.
[0026] The pH adjustment in step 2) is to adjust the pH to 9 to 11. The substances for adjusting the pH are sodium hydroxide, potassium hydroxide, ammonia water, etc.
[0027] The conditions of the hydrothermal reaction described in step 3) are a temperature of 60 to 160 °C and a time of 0.2 to 48 h; preferably a temperature of 70 to 140 °C and a time of 0.5 to 24 h, and more preferably a temperature of 70 to 120 °C and a time of 1 to 24 h.
[0028] A micro-nano needle phosphate multifunctional coating is composed of micro-nano needles formed by phosphate crystallization. The micro-nano needles have a tip shape. The bottom of the micro-nano needle coating is tightly bonded to the substrate, and the tips face outward.
[0029] The diameter of the described micro-nano needles (the diameter of the circle at the maximum cross-section) is 20 nm to 8 μm, preferably 40 nm to 5 μm; the length of the needles is 30 nm to 20 μm, preferably 100 nm to 12 μm; the tip spacing is 40 nm to 12 μm, preferably 80 nm to 6 μm.
[0030] The phosphate crystallization contains calcium salt and / or strontium salt; it may further contain zinc salt or magnesium salt.
[0031] The application of the described micro-nano needle phosphate multifunctional coating in the preparation of antibacterial, osteogenic and corrosion-slowing materials.
[0032] The present invention has the following advantages and beneficial effects:
[0033] The present invention uses a chelating agent to effectively chelate metal ions in the reaction solution, regulate the longitudinal preferential growth of grains, and form a micro-nano needle phosphate coating. The preparation process of the micro-nano needle ceramic coating in the present invention is simple, the hydrothermal reaction solution prepared is non-toxic and harmless, the prepared ceramic coating acts through contact antibacterial, is non-toxic and harmless, and will not produce side effects such as drug resistance, and is suitable for long-term medical implant devices; the prepared micro-nano structure coating has high antibacterial activity and is suitable for medical implant devices that require long-term antibacterial effects; the prepared micro-nano structure coating is a phosphate coating containing calcium, strontium, etc. Trace elements such as calcium and strontium can enhance the interaction between bone cell materials, so that its bioactivity and biocompatibility are expected to be significantly improved during the implantation process, and there is a certain osteogenic effect; in addition to having good antibacterial and osteogenic properties, the micro-nano structure can also endow the coating with good corrosion protection performance. Description of the Drawings
[0034] Figure 1 It is the surface morphology diagram of the micro-nano needle coating prepared in Example 1 under a scanning electron microscope;
[0035] Figure 2 It is the polarization curve result diagram of the modified sample and the substrate sample of the micro-nano needle coating prepared in Example 1 in artificial saliva at 37 °C;
[0036] Figure 3Antibacterial performance results of the micro-nano needle coating modified sample and the matrix sample prepared in Example 1 against Streptococcus mutans and Escherichia coli;
[0037] Figure 4 Results of the number of mouse pre-osteoblasts adhered to the surface of the micro-nano needle coating modified sample and the matrix sample prepared in Example 1;
[0038] Figure 5 Surface morphology of the coating prepared in Comparative Example 1 under scanning electron microscope;
[0039] Figure 6 Surface morphology of the coating prepared in Comparative Example 3 under scanning electron microscope. Detailed implementation mode
[0040] The present invention will be further described in detail below in conjunction with embodiments, but the implementation modes of the present invention are not limited thereto.
[0041] If the specific test conditions are not specified in the following implementation examples, they are usually in accordance with the conventional test conditions or the test conditions recommended by the reagent company. The materials, reagents, etc. used, unless otherwise specified, are all reagents and materials obtained from commercial channels.
[0042] Example 1: Preparation of a micro-nano needle strontium-based phosphate multifunctional coating on pure zinc surface
[0043] (1) Using commercially available pure zinc as the matrix material, first perform wire cutting on it, polish it with sandpaper, then ultrasonically clean it in absolute ethanol for 15 minutes, and finally rinse it with deionized water.
[0044] (2) Prepare a 142.8 mmol / L strontium nitrate aqueous solution, denoted as solution A; prepare an 89.8 mmol / L sodium dihydrogen phosphate aqueous solution, denoted as solution B; prepare a 150.0 mmol / L sodium hydroxide aqueous solution of ethylenediaminetetraacetic acid (equivalent to a sodium ethylenediaminetetraacetate solution), denoted as solution C.
[0045] (3) Add an equal volume of solution C to solution A and mix well. The resulting solution is denoted as solution D.
[0046] (4) Add an equal volume of solution B (the volume of solution B is the same as that of solution A) to solution D, and adjust the pH to 10 with sodium hydroxide to obtain a reaction solution.
[0047] (5) Immerse the matrix material treated in step (1) into the reaction solution in step (4), carry out a hydrothermal reaction at 80 °C for 3 hours, then rinse it with deionized water and dry it to obtain a micro-nano needle strontium-based phosphate coating.
[0048] Example 2: Preparation of a Multifunctional Micro-Nano-Pin Strontium-Based Phosphate Coating on the Surface of Zinc Alloy
[0049] (1) Using commercially available Zn-Al8 zinc alloy as the substrate material, first perform wire cutting on it, polish it with sandpaper, then ultrasonically clean it in absolute ethanol for 10 min, and finally rinse it with deionized water.
[0050] (2) Prepare a 35.7 mmol / L strontium nitrate aqueous solution, denoted as solution A; prepare a 22.5 mmol / L potassium dihydrogen phosphate aqueous solution, denoted as solution B; prepare a 37.5 mmol / L ethylenediaminetetraacetic acid potassium aqueous solution, denoted as solution C.
[0051] (3) Add an equal volume of solution C to solution A and mix well. The resulting solution is denoted as solution D.
[0052] (4) Add an equal volume of solution B (the volume of solution B is the same as that of solution A) to solution D, and adjust the pH to 9 with potassium hydroxide to obtain a reaction solution.
[0053] (5) Immerse the substrate material treated in step (1) into the reaction solution in step (4) above, carry out a hydrothermal reaction at 95 °C for 10 h, then rinse it with deionized water and dry it to obtain a micro-nano-pin strontium-based phosphate coating.
[0054] Example 3: Preparation of a Multifunctional Micro-Nano-Pin Calcium-Based Phosphate Coating on the Surface of Magnesium Alloy [[ID=?]]
[0055] (1) Using commercially available WE43 magnesium alloy as the substrate material, first perform wire cutting on it, polish it with sandpaper, then ultrasonically clean it in absolute ethanol for 15 min, and finally rinse it with deionized water.
[0056] (2) Prepare a 285.6 mmol / L calcium nitrate aqueous solution, denoted as solution A; prepare a 179.6 mmol / L sodium hydrogen phosphate aqueous solution, denoted as solution B; prepare a 300.0 mmol / L sodium ethylenediaminetetraacetate aqueous solution, denoted as solution C.
[0057] (3) Add an equal volume of solution C to solution A and mix well. The resulting solution is denoted as solution D.
[0058] (4) Add an equal volume of solution B (the volume of solution B is the same as that of solution A) to solution D, and adjust the pH to 11 with sodium hydroxide to obtain a reaction solution.
[0059] (5) Immerse the substrate material treated in step (1) into the reaction solution in step (4) above, carry out a hydrothermal reaction at 70 °C for 15 h, then rinse it with deionized water and dry it to obtain a micro-nano-pin calcium-based phosphate coating. It should be noted that there seems to be a missing ID value in the original text for the line "
[0055] ". This might be an oversight in the provided content. If this is a critical part for the translation, it would be beneficial to have the correct information.
[0060] Example 4: Preparation of a Multifunctional Strontium Phosphate Coating with Micro-Nano Needles on the Surface of Pure Zinc
[0061] (1) Using commercially available pure zinc alloy as the substrate material, first perform wire cutting on it, polish it with sandpaper, then ultrasonically clean it in absolute ethanol for 10 min, and finally rinse it with deionized water.
[0062] (2) Prepare a 35.7 mmol / L strontium nitrate aqueous solution, denoted as Solution A; prepare a 35.7 mmol / L potassium dihydrogen phosphate aqueous solution, denoted as Solution B; prepare a 37.5 mmol / L ethylenediaminetetraacetic acid potassium aqueous solution, denoted as Solution C.
[0063] (3) Add an equal volume of Solution C to Solution A and mix well. The resulting solution is denoted as Solution D.
[0064] (4) Add an equal volume of Solution B to Solution D and adjust the pH to 9 with potassium hydroxide to obtain a reaction solution.
[0065] (5) Immerse the substrate material treated in step (1) into the reaction solution in step (4) above, carry out a hydrothermal reaction at 120 °C for 6 h, then rinse it with deionized water and dry it to obtain a micro-nano needle strontium phosphate coating.
[0066] Comparative Example 1
[0067] (1) Using commercially available pure zinc as the substrate material, first perform wire cutting on it, polish it with sandpaper, then ultrasonically clean it in absolute ethanol for 15 min, and finally rinse it with deionized water.
[0068] (2) Prepare a 142.8 mmol / L strontium nitrate aqueous solution, denoted as Solution A; prepare an 89.8 mmol / L sodium dihydrogen phosphate aqueous solution, denoted as Solution B.
[0069] (3) Add an equal volume of Solution B to Solution A and mix well. Adjust the pH to 10 with sodium hydroxide to obtain a reaction solution.
[0070] (4) Immerse the substrate material treated in step (1) into the reaction solution in step (4) above, carry out a hydrothermal reaction at 80 °C for 3 h, then rinse it with deionized water and dry it to obtain a strontium phosphate coating.
[0071] Comparative Example 2
[0072] (1) Using commercially available pure zinc as the substrate material, first perform wire cutting on it, polish it with sandpaper, then ultrasonically clean it in absolute ethanol for 15 min, and finally rinse it with deionized water.
[0073] (2) Prepare an aqueous solution of strontium nitrate at 142.8 mmol / L, denoted as Solution A; prepare an aqueous solution of sodium dihydrogen phosphate at 8.0 mmol / L, denoted as Solution B; prepare an aqueous solution of sodium hydroxide with ethylenediaminetetraacetic acid at 150.0 mmol / L, denoted as Solution C.
[0074] (3) Add an equal volume of Solution C to Solution A and mix well. The resulting solution is denoted as Solution D.
[0075] (4) Add an equal volume of Solution B (the volume of Solution B is the same as that of Solution A) to Solution D, and adjust the pH to 10 with sodium hydroxide to obtain a reaction solution.
[0076] (5) Immerse the substrate material treated in step (1) into the reaction solution in step (4) above, carry out a hydrothermal reaction at 80 °C for 3 h, then rinse with deionized water and dry to obtain a strontium-based phosphate coating.
[0077] Comparative Example 3
[0078] (1) Use commercially available pure zinc as the substrate material. First, perform wire cutting on it, polish it with sandpaper, then ultrasonically clean it in absolute ethanol for 15 min, and finally rinse it with deionized water.
[0079] (2) Prepare an aqueous solution of strontium nitrate at 142.8 mmol / L, denoted as Solution A; prepare an aqueous solution of sodium dihydrogen phosphate at 89.8 mmol / L, denoted as Solution B; prepare an aqueous solution of sodium hydroxide with ethylenediaminetetraacetic acid at 150.0 mmol / L, denoted as Solution C.
[0080] (3) Add an equal volume of Solution C to Solution A and mix well. The resulting solution is denoted as Solution D.
[0081] (4) Add an equal volume of Solution B to Solution D, and adjust the pH to 13 with sodium hydroxide to obtain a reaction solution.
[0082] (5) Immerse the substrate material treated in step (1) into the reaction solution in step (4) above, carry out a hydrothermal reaction at 80 °C for 3 h, then rinse with deionized water and dry to obtain a strontium-based phosphate coating.
[0083] Comparative Example 4
[0084] (1) Use commercially available pure zinc as the substrate material. First, perform wire cutting on it, polish it with sandpaper, then ultrasonically clean it in absolute ethanol for 15 min, and finally rinse it with deionized water.
[0085] (2) Prepare an aqueous solution of strontium nitrate at 142.8 mmol / L, denoted as Solution A; prepare an aqueous solution of sodium dihydrogen phosphate at 89.8 mmol / L, denoted as Solution B; prepare an aqueous solution of sodium hydroxide of ethylenediaminetetraacetic acid at 150.0 mmol / L, denoted as Solution C.
[0086] (3) Add an equal volume of Solution C to Solution A and mix well. The resulting solution is denoted as Solution D.
[0087] (4) Add an equal volume of Solution B to Solution D and adjust the pH to 10 with sodium hydroxide to obtain a reaction solution.
[0088] (5) Immerse the substrate material treated in step (1) into the reaction solution in step (4) above, carry out a hydrothermal reaction at 50 °C for 3 h, then rinse with deionized water and dry to obtain a strontium-based phosphate coating.
[0089] Comparative Example 5
[0090] (1) Use commercially available pure zinc as the substrate material. First, perform wire cutting on it, polish it with sandpaper, then ultrasonically clean it in absolute ethanol for 15 min, and finally rinse with deionized water.
[0091] (2) Prepare an aqueous solution of calcium nitrate at 142.8 mmol / L, denoted as Solution A; prepare an aqueous solution of sodium dihydrogen phosphate at 89.8 mmol / L, denoted as Solution B.
[0092] (3) Add an equal volume of Solution B to Solution A, mix well, and adjust the pH to 10 with sodium hydroxide to obtain a reaction solution.
[0093] (4) Immerse the substrate material treated in step (1) into the reaction solution in step (4) above, carry out a hydrothermal reaction at 80 °C for 3 h, then rinse with deionized water and dry to obtain a calcium-based phosphate coating.
[0094] Sample Detection and Results
[0095] Figure 1 It is the surface morphology diagram of the micro-nano needle coating prepared in Example 1 under a scanning electron microscope. It can be seen that by using the hydrothermal method under the condition of adding a chelating agent, a micro-nano needle coating with a diameter of 50 nm to 4 μm, a length of 150 nm to 12 μm, and a tip spacing of 100 nm to 10 μm is successfully prepared on the surface of pure zinc. The micro-nano needles are stacked into a flower cluster shape, the coating is uniform, and no obvious defects are observed. The morphologies of the coating samples prepared in Examples 2-4 under the scanning electron microscope are similar to Figure 1 approximate.
[0096] Figure 5 and 6They are the surface morphology diagrams of the coatings prepared in Comparative Examples 1 and 3 under scanning electron microscopy. The results show that under the conditions of Comparative Example 1, no coating can be formed on the surface of the metal substrate; under the conditions of Comparative Example 3, the coating on the surface of the metal substrate is different from that of Example 1, and the adhesion of this coating is extremely poor and it falls off from the substrate even after slight scratching. It can be seen from this that specific parameter ranges are required to form a coating on the surface of the metal substrate. Micro-nano needle coatings cannot be prepared in Comparative Examples 2, 4 and 5 either.
[0097] Figure 2 It is the potentiodynamic polarization curve result diagram measured by an electrochemical workstation for the micro-nano needle coating sample and the substrate material prepared in Example 1 in artificial saliva at 37°C. From the electrochemical test results of the substrate sample and the micro-nano needle coating sample in the simulated body fluid at 37°C, compared with the substrate sample, the corrosion potential of the coating sample moves in the positive direction and has a higher corrosion potential. The corrosion current density of the coating sample decreases from 7.65 μA / cm 2 to 0.22 μA / cm 2 , which is reduced by one order of magnitude compared with the value of the substrate sample. This shows that the micro-nano needle structure coating formed on the surface of pure zinc can effectively slow down the corrosion rate of the zinc substrate, thereby slowing down the release of zinc ions and reducing the biological toxicity caused by excessive release of zinc ions. Micro-nano needle coatings cannot be prepared in Comparative Examples 1 to 5, and even the adhesion of the coatings is extremely poor and they have almost no anti-corrosion performance.
[0098] Figure 3Antibacterial activities of the micro-nano needle coating samples and substrate samples prepared in Example 1 against Streptococcus mutans. 5×105 CFU of Streptococcus mutans and Staphylococcus aureus were inoculated onto the surfaces of the coating samples and substrate samples, and after culturing in a biochemical incubator at 37°C for 3 h respectively, they were eluted with phosphate buffer solution to obtain bacterial solutions. After diluting the bacterial solutions to appropriate multiples, they were respectively subjected to plate coating, and the antibacterial rates were calculated. The experimental results showed that the antibacterial rates of the substrate against Streptococcus mutans and Escherichia coli were both higher than 95.0%, showing a relatively high antibacterial rate; the antibacterial rates of the coating-modified samples against Streptococcus mutans and Escherichia coli were higher than 91.8%, and good antibacterial performance could still be maintained after coating modification. The antibacterial performance of the zinc substrate sample group was due to the fact that zinc ions could interact with the cell membranes of microorganisms, resulting in damage to the cell membranes. This interaction might cause the rupture of the cell membranes, leading to the leakage of cell contents and ultimately the death of microorganisms; at the same time, zinc ions could also participate in biological redox reactions, resulting in the generation of toxic oxidation substances such as reactive oxygen species, showing a certain antibacterial effect. For the coating samples with micro-nano needle structures, the introduction of the coating prevented the release of zinc ions, and the cell membranes or cell walls of bacteria were damaged by sharp objects in the coating or by applying shear forces, etc. This way might lead to the rupture of the cell membranes, and then destroy the integrity and function of bacteria. Therefore, the micro-nano needle coating samples had significant antibacterial effects on typical representative Gram-positive bacteria and Gram-negative bacteria, indicating that the micro-nano needle structure was the key factor for the exertion of antibacterial function. The materials of other examples were tested by the same method, and the antibacterial effects of the micro-nano needle coatings prepared in Examples 2 to 4 were similar to that of Example 1.
[0099] In Comparative Examples 1 and 5, coatings could not be formed, and their antibacterial effects were the antibacterial effects of the substrate, but the excessive release of zinc ions from the substrate would bring biological toxicity. In Comparative Examples 2 to 4, the micro-nano needle structures of Example 1 could not be obtained, and the binding force between the prepared coatings and the substrate was extremely poor. When contacting with the bacterial solution, the coatings would fall off, and the antibacterial effects basically came from the substrate, but the excessive release of zinc ions from the substrate would bring biological toxicity.
[0100] In addition, non-needle-shaped coatings containing strontium or calcium basically had no antibacterial effect.
[0101] For implantable medical devices, in addition to having excellent antibacterial performance, good biocompatibility is also extremely crucial. Figure 4 Results graph of the number of mouse pre-osteoblasts adhered to the surfaces of the micro-nano needle coating-modified samples and substrate samples prepared in Example 1. The 10 mm×10 mm×5 mm coating-modified samples and substrate were disinfected with 75% ethanol and placed in a 24-well cell culture plate. 50,000 MC3T3-E1 mouse pre-osteoblasts were respectively added into the above sample wells, and the cell nuclei were stained with 4',6-diamidino-2-phenylindole staining agent. After culturing for 12 h, the number of cells on the sample surfaces was observed under a fluorescence microscope and statistically calculated. FromFigure 4 The results show that the number of adhered cells on the surface of the pure zinc substrate is extremely small. This is because the excessive zinc ions released on the surface of the zinc specimen can cause damage to cells such as oxidative stress, apoptosis, changes in membrane permeability, and impaired enzyme activity, showing obvious cytotoxicity. In contrast, the number of adhered cells on the coated and modified samples is significantly increased. This indicates that the modified sample group can not only effectively reduce the degradation rate of zinc ions in the oral environment, but also effectively improve the cytocompatibility of the zinc substrate by slowing down the release of zinc ions. The coating exhibits good biocompatibility, which is crucial for implantable medical devices.
[0102] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and are all included in the protection scope of the present invention.
Claims
1. A method for preparing a micro-nano needle phosphate antibacterial multifunctional coating, characterized by: The following steps are involved: 1) using water to prepare solutions of metal salt, phosphate and chelating agent respectively; 2) mixing the chelating agent solution with the metal salt solution to obtain a mixed solution; mixing the phosphate solution with the mixed solution and adjusting the pH to 8 to 12 to obtain a reaction solution; 3) Immersing the clean substrate material in the reaction solution for hydrothermal reaction to obtain a micro-nano needle phosphate coating on the surface of the substrate material; The conditions of the hydrothermal reaction are a temperature of 60 to 160° C. and a time of 0.2 to 48 hours; The metal salt in step 1) comprises at least one of strontium nitrate, strontium chloride, calcium nitrate, and calcium chloride; The phosphate in step 1) is at least one of potassium dihydrogen phosphate, potassium hydrogen phosphate, potassium phosphate, sodium dihydrogen phosphate, sodium hydrogen phosphate, sodium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; The molar ratio of the metal salt, phosphate and chelating agent in step 2) is 5-1000:3-600:5-1000.
2. The method for preparing the micro-nano needle phosphate antibacterial multifunctional coating according to claim 1, characterized in that: The chelating agent in step 1) is at least one of ethylenediaminetetraacetic acid, ethylenediaminetetraacetic acid disodium, ethylenediaminetetraacetic acid trisodium, ethylenediaminetetraacetic acid tetrasodium, ethylenediaminetetraacetic acid dipotassium, ethylenediaminetetraacetic acid tripotassium, ethylenediaminetetraacetic acid tetrapotassium, ethylenediaminetetraacetic acid diammonium, ethylenediaminetetraacetic acid triammonium, ethylenediaminetetraacetic acid tetraammonium, ethylenediaminetetraacetic acid sodium iron, iminodisuccinic acid, iminodisuccinic acid tetrasodium, iminodisuccinic acid potassium and other iminodisuccinic acids and salts, diethylenetriamine pentaacetic acid, diethylenetriamine pentaacetic acid sodium, ethylene glycol bis-2-aminoethyl ether tetraacetic acid, ethylene glycol bis-2-aminoethyl ether tetrasodium, and ethylene glycol bis-2-aminoethyl ether tetrapotassium.
3. The method for preparing the micro-nano needle phosphate antibacterial multifunctional coating according to claim 2, characterized in that: The pH in step 2) is 9 to 11; The conditions of the hydrothermal reaction in step 3) are a temperature of 70 to 140° C. and a time of 0.5 to 24 h; In step 2), the molar ratio of the metal salt in the metal salt solution, the phosphate in the phosphate solution and the chelating agent in the chelating agent solution is (0.5-5):1:(0.5-5).
4. The method for preparing the micro-nano needle phosphate antibacterial multifunctional coating according to claim 3, characterized in that: The conditions of the hydrothermal reaction in step 3) are a temperature of 70 to 120° C. and a time of 1 to 24 hours; The molar ratio of the metal salt, phosphate and chelating agent in step 2) is (1-2.5):1:(1-2.5).
5. The method for preparing the micro-nano needle phosphate antibacterial multifunctional coating according to claim 1, characterized in that: The metal salt in step 1) may or may not include at least one water-soluble salt containing biologically active elements such as magnesium, zinc, manganese, copper, silver, silicon, fluorine, cobalt, and selenium; The concentration of the metal salt solution in step 1) is 5 to 1000 mmol / L; The concentration of the phosphate solution in step 1) is 3 to 600 mmol / L; The concentration of the chelating agent solution in step 1) is 5 to 1000 mmol / L.
6. The method for preparing the micro-nano needle phosphate antibacterial multifunctional coating according to claim 5, characterized in that: The concentration of the metal salt solution in step 1) is 10 to 800 mmol / L; The concentration of the phosphate solution in step 1) is 6 to 500 mmol / L; The concentration of the chelating agent solution in step 1) is 10 to 800 mmol / L.
7. The method for preparing the micro-nano needle phosphate antibacterial multifunctional coating according to claim 1, characterized in that: The matrix material in step 3) is at least one of zinc, zinc alloy, magnesium, magnesium alloy, iron, iron alloy, titanium, titanium alloy, tantalum, tantalum alloy, aluminum, aluminum alloy, or porous materials corresponding to the above materials or materials subjected to the above metal surface treatment; The clean base material in step 3) is obtained by cleaning the base material; The cleaning is to use at least one of detergent, cleaning powder and organic solvent to clean the base material.
8. The micro-nano needle phosphate antibacterial multifunctional coating obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The micro-nano needles are composed of micro-nano needles formed by phosphate crystals. The micro-nano needles have needle tips, and the bottom of the micro-nano needle coating is tightly combined with the substrate.
9. The micro-nano needle phosphate antibacterial multifunctional coating according to claim 8, characterized in that: The diameter of the micro-nano needle is 20nm-8μm; the length of the needle is 30nm-20μm; and the distance between the needle tips is 40nm-12μm.
10. The use of the micro-nano needle phosphate antibacterial multifunctional coating according to claim 8 or 9, characterized in that: The coating is used for preparing antibacterial materials, medical implant materials or corrosion protection materials.